(untitled) (Web of Teachers: Inderscience Research, 2024)
This article discusses the principles of deontological ethics, a moral theory that emphasizes adherence to moral rules or duties regardless of their consequences. While traditionally associated with philosophical discourse, this paper seeks to explore deontology through the lens of scientific perspectives. Drawing from insights in neuroscience, evolutionary psychology, and behavioral economics, we investigate how scientific research provides empirical support for the principles underlying deontological moral reasoning. Through studies employing brain imaging techniques, evolutionary theory, and behavioral experiments, scientists have elucidated the cognitive mechanisms and innate moral intuitions that shape human moral judgments. By integrating these findings with the principles of deontology, we aim to shed light on the complex interplay between rationality, emotion, and moral duty in human decision-making.